Utilizing Disclosure Analysis to Bridge ESG Implementation Gaps: A Study Case PT XCXIND - Ade Rochman HN; Neneng Nurlaela Arief (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The rise of sustainability goals globally has placed the Environmental, Social and Governance (ESG) framework as a crucial benchmark in measuring corporate performance. This study evaluates the ESG implementation and compliance of PT XCXIND, a major player in Indonesia's nickel industry, which plays a pivotal role in the advancement of clean energy. Through content analysis of the sustainability report issued by PT XCXIND in 2023, and ESG ratings issued by Sustainalytics, LSEG, S&P Global, and SRI-KEHATI, complemented by interviews with experts, this study identifies achievements and areas of improvement in ESG practices. PT XCXIND has shown excellence in environmental initiatives, such as the use of renewable energy, reduction of carbon emissions and biodiversity conservation. However, there are still some challenges in terms of social equity and governance such as stakeholder engagement and governance transparency. This study proposes strategic recommendations to improve ESG performance by focusing on sustainable innovation, carbon management, social responsibility and improved governance. Strengthening these areas will improve PT XCXIND's ESG rating, increase investor confidence and support long-term sustainability goals.